Determinants of the non-performing loan ratio in the European Union banking sectors with a high level of impaired loans - Ciukaj, Radosław; Kil, Krzysztof (Economics and Business Review, 2020)
In the article an attempt is made to identify the quality of credit exposure determinants of banks in European Union countries that were characterized by a high level of impaired loans at the end of 2017 (Bulgaria, Croatia, Cyprus, Italy, Ireland, Greece, Portugal). Using the static panel-based approach the non-performing loan (NPL) determinants for the period from 2011 to 2017 were analyzed. The results showed that the high level of NPLs can be explained mainly by both macroeconomic and microeconomic factors. In particular, it has been shown that in the surveyed countries supervisory authorities should pay special attention to smaller banks with high dynamics of new loans and a low return on assets due to the fact that these entities are characterized by a higher NPL ratio. A higher level of NPL is also affected by a high concentration of the banking sector and higher interest rates on newly granted loans. As a result of research it was also shown that the majority of NPL determinants are the same in all types of banks, regardless of the business model and the scope of banking supervision. The differences were noticeable in characteristics regarding the housing market as well as the profitability of operations and lending dynamics of the analyzed entities.